Treatment of Skin Oncological Disease Using an Immunosuppressive Medication - Mikazans, Ingmars; Hartmane, Ilona; Scerbuks, Mihails; Ivdra, Iveta; Saulite, Ieva; Bondare-Ansberga, Vanda; Lapsins, Artis (Gaceta Médica de Caracas, 2023)
Skin cancer or non-melanoma malignant formations, as well as melanomas, are recorded in more than 2-3 million people every year. The most important cause of the occurrence of this disease is the effect of UV radiation on damaged areas of the skin, birthmarks, or sensitive skin (light, capable of burning). Dermatoscopy is one of the most important methods for determining the stage of tumor development, and the simplest method of treatment in the initial stages is the use of immunosuppressive agents that reduce the work of the immune system by preventing the formation of antibodies.